Parathyroid cysts: A review of 359 patients reported in the international literature. Issue 28 (July 2018) - Papavramidis, Theodosios S.; Chorti, Angeliki; Pliakos, Ioannis; Panidis, Stavros; Michalopoulos, Antonios
Abstract: Background: Parathyroid cysts are lesions that represent 1–5% of neck masses. They are subdivided into two categories: functioning and non-functioning. The aim of the present review is to give a detailed account of all reported cases of parathyroid cysts in the literature and to analyze statistically the available data. Methods: A bibliographic research was performed from 1905 until 2016. A database with the patients' characteristics was made and analyzed statistically. Results: A total of 218 articles were found, reporting 359 cases of cysts. Mean age of patients was 49.24 y/o and the male/female ratio was 1:1.85. The most common locations were left thyroid lobe (113/358 patients, 31.6%), and superior mediastinum (69/358 patients, 19.3%), while the most common symptoms were neck mass (148/355 patients, 41.7%), compressive symptoms (73/355 patients, 206%) and hyperparathyroidism (62/355 patients, 17.5%). Non-functioning cysts were more frequent (220/357 patients, 61.6%). Regarding dimensions, mean diameter was 4.88 cm. Ultrasound and FNA are used for their diagnosis, while cystic fluid analysis may help the differential diagnosis. Recurrences were mentioned in 27/97 patients (27.8%) with available data. No deaths due to parathyroid cysts were mentioned in the literature. Conclusion: Parathyroid cysts should be taken into consideration in case of parathyroid dysfunction or asymptomatic neck mass. The surgeon's careful manipulations on the cyst are crucial for a definitive treatment.